Building Automation System (BAS) implementation: A literature review - Escobar, Diego; Garcia, Francisco; Cadena-Gaitan, Carlos (2013)
Building Automation System (BAS) also known as Building Management System (BMS), are principally integrated processor based on systems.In principle, a Building Automation System (BAS) or digital controller is a micro-computer system specially designs to be suitable for data acquisition, control and communication and others.The Building Automation System (BAS) function is to control and monitor all building access using computerized system.Most of the automation system is behind the scenes as hardware devices mounted to equipment of hidden under floor or in the ceiling.BAS device is to control the services in the building at the different area.Building Automation System (BAS) can be considered as a tool in the hands of building operation personnel that provide a more effective and efficient control overall building systems.The purpose of this paper is to determine the function of Building Automation System (BAS),controller system and barriers of the Building Automation System (BAS) implementation.The study used an approach that is secondary data implemented through literature review from books,journals, website and others.This paper will produce the function of BAS, controller system and the barriers of BAS implementation in the building.The barriers are based on the literature and observation.There are five significant barriers of BAS. These barriers are cost, followed by installation, usage and marketing of the BAS.The study aims is to determine the function, controller system and to identify the barrier of the BAS implementation.